NHÂN VẬT NGUYỄN DU TỪ THƠ ĐẾN TIỂU THUYẾT - Nguyễn, Thị Thẩm Mỹ (Trường Đại học Đà Lạt, 2023)
On the basis of learning and analyzing Chinese poems by Nguyen Du and the novel about this great poet by Nguyen The Quang, the author of this article ventures to clarify the similarities and differences of the character Nguyen Du between poetry and the aforementioned novel. Such differences can shed light on the innovations, creativity, and contributions of Nguyen The Quang in the process of establishing the historical character of Nguyen Du and the dynamics of modern Vietnamese novels, especially in the subcategory of historical novels.